In Utero Exposure to Dolutegravir-Based Antiretroviral Therapy Alters Growth and Metabolic Outcomes - Niyati Patel; Abhayavarshini Shridhar; Ryan D Ross (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Approximately 5,000 women living with HIV give birth each year, with perinatal transmission occurring in less than 1% of cases. The World Health Organization (WHO) recommends dolutegravir (DTG) as first and second line antiretroviral therapy (ART), readily crossing the placenta, resulting in persistent exposure throughout development. In adults, DTG-based ART has been linked to metabolic changes, including alterations in bone mineral density and body composition. The effects of DTG exposure on bone development and body composition trajectories in HIV-exposed uninfected (HEU) children are currently unknown. Methods Female C57BL/6J mice (8–10 weeks old) were mated with 3–4-month-old males. Dams were assigned to either dolutegravir/tenofovir disoproxil fumarate/lamivudine (DTG/TDF/3TC) infused pellets (ART) or control pellets from mating until weaning at postnatal day (PND) 28. Offspring body weights were recorded from PND15 to 86. Body composition was assessed using DEXA at PND36 and PND50. At PND28, circulating leptin and adiponectin were measured, and visceral adipose tissue gene expression (leptin and PPARγ) was assessed by qPCR. Results Maternal exposure to DTG-based ART was associated with increased body weight in both sexes, with larger differences in males (PND36: Males 20.28 ± 0.6 g vs 19.16 ± 0.5 g, p = 0.03; Females 17.15 ± 0.4 g vs 16.41 ± 0.3 g, p = 0.05). DEXA analysis demonstrated higher lean mass (PND50: Males 11.5 ± 0.4 cm2 vs 11.0 ± 0.3 cm2, p = 0.04; Females 10.8 ± 0.3 cm2 vs 10.4 ± 0.2 cm2, p = 0.08) and increased fat area (PND50: Males 4.0 ± 0.2 cm2 vs 3.5 ± 0.2 cm2, p = 0.02; Females 3.3 ± 0.1 cm2 vs 3.0 ± 0.1 cm2, p = 0.07) in ART-exposed pups compared to controls. Bone mineral content was elevated in ART-exposed offspring at PND36 and PND50 (PND50: Males 0.55 ± 0.02 g vs 0.48 ± 0.02 g, p = 0.01; Females 0.50 ± 0.01 g vs 0.44 ± 0.01 g, p = 0.02). Serum adiponectin showed a significant increase in ART-treated males (p = 0.02), with a trend toward increased circulating leptin in both treated sex groups. Visceral adipose tissue showed greater adipocyte differentiation in control pups, supported by elevated leptin and PPARγ expression. Conclusion Perinatal exposure to DTG/TDF/3TC during pregnancy and breastfeeding alters growth, body composition and adipose transcriptional profiles in offspring. This suggests maternal ART may shape early-life metabolic programming, highlighting the importance of monitoring outcomes in HEU children.